Application of participatory rural appraisal methods for action research on water management - Gosselink, P.; Thompson, J. (International Irrigation Management Institute, 1997)
This report summarizes recent experiences with the application of PRA methods in the fields of irrigation and water management in Sri Lanka, Pakistan, India, Kenya, Estonia, and Zimbabwe. Methods of group dynamics, sampling, semi-structured interviewing and dialogue, visualization and diagramming are explained, with examples. The authors attempt to clarify some confusion about PRA that exists, and offer several recommendations about how it can be used-not as a replacement but as a complement to other conventional methods of appraisal-to en-hance processes of research and development in the fields of irrigation and water management in developing areas.